Comparison of Impact of Cultural Intelligence Between Cultural Orientations and Conflict Management Styles: A Case of Multi Countries (Journal of Asian Development Studies, 2024)
In today's globalised work environment, organisations frequently encounter cultural diversity, which can foster innovation but also lead to conflict. This study examines the influence of Cultural Values and Orientation (CVO) on Conflict Management Styles (CMSs)—specifically, avoidance, forcing, and problem-solving—while investigating the moderating role of Cultural Intelligence (CQ). Drawing on Hofstede's cultural dimensions (power distance, uncertainty avoidance, collectivism, masculinity, and long-term orientation) and four CQ components (meta-cognitive, cognitive, motivational, and behavioural), the study examines how individuals' cultural traits influence their preferences for conflict resolution in multicultural workplaces. Data were collected from 1,012 organizational employees across Pakistan, Germany, and the USA using validated Likert-scale instruments. The results from structural equation modelling (using AMOS-26) confirm that cultural values significantly predict conflict management behaviour, and that CQ moderates these relationships. For example, individuals with high power distance tend to be inclined toward avoidance and force, while those with high collectivism and long-term orientation prefer problem-solving. Significantly, high CQ levels enhance cooperative resolution tendencies and mitigate aggressive responses. These findings underscore the importance of fostering CQ in multicultural teams to improve conflict resolution and organizational harmony. This research contributes to both theory and practice by integrating culture-specific values with individual capabilities in managing workplace conflict effectively.